2012
DOI: 10.2134/agronj2011.0355
|View full text |Cite
|
Sign up to set email alerts
|

Soil and Crop Response to Wood Ash and Lime Application in Acidic Soils

Abstract: Wood ash has the properties to be an effective liming material, and research is needed to compare its effectiveness relative to agricultural lime on acidic agricultural soils. Wood ash at a calcium carbonate rate of 6.72 t ha−1 was compared with an equivalent rate of agricultural lime on a clay loam soil with an initial pH of 4.9. Replicated plots were managed under a barley (Hordeum vulgare L.)–canola (Brassica rapa L.)–pea (Pisum sativum L.) rotation for 4 yr (2002–2005). Soil pH increased in the order of: w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
24
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 29 publications
(44 reference statements)
5
24
0
7
Order By: Relevance
“…Wood ash, the solid by-product of wood incineration, has several proven beneficial effects on soils, such as an increase in soil pH and added nutrient value (Bougnom et al 2009(Bougnom et al , 2012Klemedtsson et al 2010;Pérez-Cruzado et al 2010;Arshad et al 2012;Saarsalmi et al 2012;Podmirseg et al 2013). This has been shown, in some cases, to lead to improved crop productivity (Pérez-Cruzado et al 2010;Bougnom et al 2012;Materechera 2012;Moilanen et al 2012;Saarsalmi et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Wood ash, the solid by-product of wood incineration, has several proven beneficial effects on soils, such as an increase in soil pH and added nutrient value (Bougnom et al 2009(Bougnom et al , 2012Klemedtsson et al 2010;Pérez-Cruzado et al 2010;Arshad et al 2012;Saarsalmi et al 2012;Podmirseg et al 2013). This has been shown, in some cases, to lead to improved crop productivity (Pérez-Cruzado et al 2010;Bougnom et al 2012;Materechera 2012;Moilanen et al 2012;Saarsalmi et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In western Canada, forage yield was higher with wood ash than with lime plus P fertilizer (Lickacz, 2002); lime and wood ash increased microbial biomass and C mineralization, and changed the functional structure of bacterial communities (Lupwayi, Arshad, Azooz, & Soon, 2009); and the increases were wood ash = lime for soil pH, and wood ash > lime for the available P, aggregation of soil and yield of barley, canola and field pea (Arshad, Soon, Azooz, Lupwayi, & Chang, 2012). Greater increase in crop yield with wood ash compared with lime in these studies was attributed to a more rapid change in soil pH, and increased P availability.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lickacz (2002) stated that the range of percent calcium carbonate equivalent (%CCE) of wood ash is generally 55 to 65 with some facilities up to 100%. Wood ash used by Erich & Ohno (1992) contained 12.1 g kg -1 total P, 18 g kg -1 total K, and 10.7 g kg -1 total Mg; and wood ash used by Arshad et al (2012) had 0.26 g NO 3 -N kg -1 and 0.93 g P kg -1 . A review by Vance (1996) showed a wide range of macronutrient (P, K, Ca, Mg, N) and micronutrient (Mn, Cu, Zn, B, Mo) concentrations in wood ash from different sources; e.g., the P concentration in 24 samples ranged from 0.3 to 14.4 g P kg -1 with a median value of 4.2 g P kg -1 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations